2010
DOI: 10.1021/om100126t
|View full text |Cite
|
Sign up to set email alerts
|

Redox Isomerization of Allylic Alcohols Catalyzed by Osmium and Ruthenium Complexes Containing a Cyclopentadienyl Ligand with a Pendant Amine or Phosphoramidite Group: X-ray Structure of an η3-1-Hydroxyallyl-Metal-Hydride Intermediate

Abstract: Complexes [MCl 2 (η 6 -p-cymene)] 2 (M = Os (1a), Ru (1b)) react with Li(C 5 H 4 CH 2 CH 2 NHMe) (LiCp N ) and KPF 6 to give the sandwich derivatives [M(η 5 -Cp N )(η 6 -p-cymene)]PF 6 (M = Os (2a), Ru (2b)). Treatment of 2a and 2b with (2,2 0 -biphenol)PCl leads to [M(η 5 -Cp P )(η 6 -p-cymene)]PF 6 (M = Os (3a), Ru (3b); Cp P = C 5 H 4 CH 2 CH 2 N(Me)P(2,2 0 -biphenol)). The photolysis of 2a, 2b, 3a, and 3b in acetonitrile produces the release of the p-cymene group and the coordination of the cyclopentadieny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 135 publications
0
34
0
1
Order By: Relevance
“…In particular, given the good results obtained with the ruthenium-guanidinate derivatives A and B (Figure 1) in the redox isomerization of allylic alcohols, we ini- tially focused on this catalytic transformation. It should be mentioned at this point that, although the osmium complexes have been much less studied than the ruthenium complexes, [10] the recent work of Esteruelas [11] and Baratta [12] and their co-workers has demonstrated that efficient catalysts can also be obtained from this metal (TOF up to 460 h -1 ). However, the catalytic activities observed for 3a-m in the isomerization of the model substrate 1-octen-3-ol were very disappointing.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, given the good results obtained with the ruthenium-guanidinate derivatives A and B (Figure 1) in the redox isomerization of allylic alcohols, we ini- tially focused on this catalytic transformation. It should be mentioned at this point that, although the osmium complexes have been much less studied than the ruthenium complexes, [10] the recent work of Esteruelas [11] and Baratta [12] and their co-workers has demonstrated that efficient catalysts can also be obtained from this metal (TOF up to 460 h -1 ). However, the catalytic activities observed for 3a-m in the isomerization of the model substrate 1-octen-3-ol were very disappointing.…”
Section: Resultsmentioning
confidence: 99%
“…[21] Moreover, incorporationo fd euterium at Ca cannoto ccur through mechanism C ([D 1 ]2p in Scheme 4). In addition, the excellent yields for both primary and sec-alcohols contrast with those reported in isomerizations through mechanism C. [19] The crossover experiments also rule out mechanism A,s ince it necessarily involvesn on-bound[ IrÀH] species, which would result in deu-Scheme1.Isomerization of opiates.…”
mentioning
confidence: 96%
“…An alternative mechanism C,v ia p-allyl intermediates, was also considered. [19] Isotopic labeling investigations were performed with sec-alcohols 1l and 1p and with primary alcohols 1x and 1z.I somerization of [D 1 ]1l afforded [D 1 ]2l,w ith deuterium exclusively at Cb (Scheme 4). In contrast, deuterium was found at both Ca and Cb in [D 1 ]2p.F or primary [D 2 ]1z,d euterium was not detected at Ca and one deuterium was exclusively transferred to Cb (see the Supporting Information).…”
mentioning
confidence: 99%
“…Da Übergangsmetalle die Verschiebung von C- C-Doppelbindungen katalysieren, kann der Allylalkohol in ein Enol überführt werden, das dann über Keto-Enol-Tautomerie in die entsprechende Carbonylverbindung übergeht. [11] Neben Rhodiumkomplexen finden besonders Rutheniumkomplexe Anwendung in der atomçkonomischen Redoxisomerisierung. [12] Die Reaktion wurde bereits sowohl in vielen großtechnischen Mehrstufensynthesen [13] als auch in der Dendrimerkatalyse [14] erfolgreich angewendet.…”
unclassified